The examination of the social dimension of shari`ah from the viewpoint of maqasid al-Shari`ah: a case study of the preservation of intellect - Shihan, Mohammad; Amanullah, Muhammad; Zaroum, AbdulHamid Mohamed Ali (IJSSHR, 2023)
Some people criticize that the classic Fiqh literature mostly focuses on generating ruling to meet the requirements of individuals rather than the community. This drives the society toward individual sense and turns their attention towards the perfection of personal rituals. On the contrary, the ShariÑah generally aims at both the community and individuals, when it requests the application of SharÊÑah rulings and commands. Because the fundamental intent of Islamic law is to regulate the Muslim community’s affairs by achieving benefit to it and averting harm from it. Accordingly, an objective approach to the texts of SharÊÑah has given rebirth to the communal perspective since the ultimate objective of SharÊÑah is to preserve social function and order and perpetuate its well-being and integrity. Therefore, this article aims to scrutinize the social dimension of ShariÑah and how it vanished from Islamic scholarship, and chiefly how it was re-emerged with the rebirth of MaqÉsid al-ShariÑah in the twentieth century. Hence, the research has taken the example of the hifz al-aql to illustrate further this vital subject. Accordingly, this article follows the qualitative method of data collection and analysis. Consequently, the research anticipates that the social dimension of Islamic ShariÑah vanished, and the juristic realm’s focus was on individual and family matters. Thus, the contemporary scholarship in the field of MaqÉsid al-ShariÑah significantly brought changes and turned into the realm of community, where it has proposed new objectives concerned with society.